1998
DOI: 10.1177/002221949803100305
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction of College Graduates with Learning Disabilities

Abstract: Job satisfaction, as assessed via five scales that posed questions concerning colleagues, work, supervision, pay, and promotion, as well as overall total job satisfaction, was examined for 55 self-identified college graduates with learning disabilities (LD) and 55 control graduates matched by gender, major, degree, and graduation year. All participants graduated from a competitive midwestern university from 1987 to 1994 and represented advantaged groups when compared to both LD and non-LD populations. The grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
7
28
0
1
Order By: Relevance
“…At this college, the findings in this study indicate that there is a significant difference in academic performance between these two groups as measured by GPA. This study, therefore, replicates the findings of Witte et al (1998).…”
Section: Findings and Recommendationssupporting
confidence: 91%
See 1 more Smart Citation
“…At this college, the findings in this study indicate that there is a significant difference in academic performance between these two groups as measured by GPA. This study, therefore, replicates the findings of Witte et al (1998).…”
Section: Findings and Recommendationssupporting
confidence: 91%
“…Witte, Philips, and Kakela (1998) found that students with learning disabilities (LD) at Miami University, a liberal arts institution in Ohio, graduated with grade point averages (GPAs) significantly below the comparison group of students without disabilities. They also found that these students with LD, on average, took one semester longer to graduate.…”
Section: Academic Performancementioning
confidence: 99%
“…Perry et al (2000) found no relationship between disability status and job satisfaction. Other studies have revealed that employees with disabilities generally have lower levels of job satisfaction than non-disabled workers (Uppal 2005;Witte et al 1998). While the evidence somewhat mixed, it tends to favor lower job satisfaction among disabled workers.…”
Section: Job Satisfactionmentioning
confidence: 93%
“…Findings from different institutions of higher education have revealed that most students are employed and have to cope simultaneously with studies and a workload (Greenbaum et al, 1996;Witte et al, 1998;Madaus et al, 2002). Approximately 80% of the adults with LD were employed full time (Adelman & Vogel, 1990); most of them reported that their LD affected their work and other aspects of their life (Greenbaum et al, 1996).…”
Section: Stress Factorsmentioning
confidence: 99%